THE EFFECTIVENESS OF CHARADES GAME TOWARD STUDENTS’ VOCABULARY MASTERY AT FOURTH GRADE OF SD UNGGULAN AISYIYAH BANTUL IN THE ACADEMIC YEAR OF 2016/2017 - Demita Sari; Noor Chairani (Universitas Ahmad Dahlan)
This research is intended to find out the students’ vocabulary mastery in experimental group who is taught by using Charades Game and in control group who is taught without using Charades Game and to find out whether there is a significant difference in English vocabulary mastery between the students in control group and the students in experimental group.The experimental research was used in this research. The subjects of this research were conducted at fourth grade students of SD Unggulan Aisyiyah Bantul Yogyakarta. They were divided into four classes. There are two classes namely experimental group and control group that was taken in experimental research. The experimental group (IV B) consists of 31 students and the control group (IV D) also consists of 31 students. The data were collected by using vocabulary test.The researcher used descriptive and inferential analysis to analyze the data, including the normality, homogeneity, and hypothesis test. The result of the pre-test showed mean score in experimental group is 54.67, while the mean of control group is 52.25. After the treatment, the mean score of the post-test in experimental group showed 81.77 and the mean score of control group showed 70.16. It means that the mean score of vocabulary mastery test of experimental group is higher than the mean score of control group. Then, the result of hypothesis using Indepentent T-test in the post-test showed that the level of significance is lower than 0.05. i.e. 0.000 < 0.05. Thus, H1 is accepted and H0 is rejected. So, it can be stated that the use of Charades game has a good effect on students’ vocabulary mastery.